2020
DOI: 10.3390/agronomy10070937
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of Different Plant Seeds with Zinc and Assessment of Health Risk of Zn-Fortified Sprouts Consumption

Abstract: Zinc (Zn) is a nutrient that regulates many vital functions of the human body, hence the demand for Zn in the balanced daily nutrition has to be covered. Priming of seeds with Zn for Zn-enriched sprout production can be considered a good alternative to artificial supplementation in a modern diet. Hence, the aim of our study was to determine the exposure level of Zn bringing neither risk for humans nor growth inhibition of enriched broccoli, pea and sunflower sprouts. Seeds treated with 0, 10, 20 and 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 41 publications
2
7
0
Order By: Relevance
“…Our results agree with Mun et al [46] for three cultivars of red bean 7-day sprouts (2.88 ± 0.03-6.32 ± 0.03 mg/100 g DM). Zinc content in 5-day-old pea sprouts, observed by Bączek-Kwinta et al [47], was comparable…”
Section: Concentration Of Trace Elements In Sproutssupporting
confidence: 80%
See 1 more Smart Citation
“…Our results agree with Mun et al [46] for three cultivars of red bean 7-day sprouts (2.88 ± 0.03-6.32 ± 0.03 mg/100 g DM). Zinc content in 5-day-old pea sprouts, observed by Bączek-Kwinta et al [47], was comparable…”
Section: Concentration Of Trace Elements In Sproutssupporting
confidence: 80%
“…Our results agree with Mun et al [46] for three cultivars of red bean 7-day sprouts (2.88 ± 0.03-6.32 ± 0.03 mg/100 g DM). Zinc content in 5-day-old pea sprouts, observed by B ączek-Kwinta et al [47], was comparable (4.54 ± 0.17 mg/100 g DM) to our study, while the study of Zou et al [48] for 5-day-old soybean sprouts indicated a lower concentration of zinc (3.2 ± 0.1 mg/100 g DM) in comparison to our study. The content of zinc in 4-day Adzuki, soybean, and mung bean sprouts (2.50 ± 0.06, 4.66 ± 0.09, 2.70 ± 0.08 mg/100 g DM, respectively) was lower than that obtained in our experiment [19], while for lentil and fenugreek (3.49 ± 0.35 mg/100 g DM) sprouts, the zinc level was of comparable value to our results [20].…”
Section: Concentration Of Trace Elements In Sproutssupporting
confidence: 79%
“…Enrichment of seeds with Zn through nutri-priming generally increases the fresh yield and dry biomass by increasing germination, seed vigor, and establishment, and improved plant-water relations (Prom-u-thai et al, 2012;Montanha et al, 2020). However, above a certain threshold, which may be crop-specific, Zn enrichment can negatively affect crop yield (Baczek-Kwinta et al, 2020). Baczek-Kwinta et al (2020) used random amplification of polymorphic DNA (RAPD) markers to evaluate the effect of Zn on sprouts of different species and observed higher DNA variation in pea sprouts when seeds were soaked overnight in 30 ppm of Zn solution compared to the seeds soaked in Zn-free solution.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting aspect to consider in this case is that during the nutrient priming process, soaking the seeds can reduce the concentration of antinutrient compounds, such as phytic acid, via leakage ( West et al., 1994 ; Egli et al., 2002 ). Very little research is available on the biofortification of vegetables via nutrient priming ( Zou et al., 2014 ; Przybysz et al., 2016 ; Bączek-Kwinta et al., 2020 ). Microgreens could be an excellent choice for nutrient biofortification by nutrient priming since they are consumed at an early seedling stage, and nutrients can rapidly translocate from seed to greens ( Di Gioia et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The HQ was calculated according to the protocol described by the Environmental Protection Agency [37], using the following equation: HQ = ADD/RFD, where ADD is the average daily dose of Zn (mg of Zn/kg body weight/day), and RFD is the recommended dietary tolerable upper intake level of Zn (mg of Zn/kg body weight/day). The I RFD value for a 70 kg adult is 3 × 10 −1 mg Zn/kg/day [38]. The ADD for 100 g portions of rocket or purslane was computed as follows: ADD = (MI × CF × DI)/BW.…”
Section: Percentage Of Recommended Daily Allowance and Hazard Quotien...mentioning
confidence: 99%